Cytometry of apoptosis. Historical perspective and new advances - Wlodkowic, D.; Skommer, J.; Darzynkiewicz, Z. (Experimental Oncology, 2012)
Characteristic changes in cell morphology paralleled by the appearance of a multitude of molecular and biochemical markers occur during apoptosis. These changes vary depending on the cell type, mechanism of induction of apoptosis, and the time-window at which the process of apoptosis is analyzed. By virtue of the capability of rapid measurement of individual cells the flow- and imaging-cytometry become preferred technologies to detect, identify and record incidence of apoptosis in large cell populations. It also provided a valuable tool to investigate molecular mechanisms in field of necrobiology. This review outlines the progress in development of the most commonly used cytometric methods probing cells death based on analysis of fragmentation of DNA, activation of caspases, analysis of mitochondrial potential, alterations in plasma membrane structure and other features that characterize programmed cell death. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”